2016
DOI: 10.1038/srep29451
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the sensitivity of life history traits to climate change in a temporary pool crustacean

Abstract: Temporary pool inhabitants face altered inundation regimes under climate change. While their exposure to these changes has received considerable attention, few studies have investigated their sensitivity or adaptability. Here, we use zooplankton as a model to explore how decreasing hydroperiods affect extinction risks and assess whether changes in life history traits could promote persistence. For this, we construct a three-stage matrix population model parameterised with realistic life-history values for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Recent publications have predicted that climate change and associated ecological processes (e.g. increased competition or predation) will change population life histories and spatial distributions (Swain et al 2015;Pinceel et al 2016;Lancaster et al 2017). In addition, climate change and other anthropogenic disturbances that alter population cycles, such as harvesting, have been shown to influence the spatial synchrony of populations, with uncertain consequences for their future (Bjørnstad 2000;Vasseur & Fox 2009;Defriez et al 2016;Shestakova et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have predicted that climate change and associated ecological processes (e.g. increased competition or predation) will change population life histories and spatial distributions (Swain et al 2015;Pinceel et al 2016;Lancaster et al 2017). In addition, climate change and other anthropogenic disturbances that alter population cycles, such as harvesting, have been shown to influence the spatial synchrony of populations, with uncertain consequences for their future (Bjørnstad 2000;Vasseur & Fox 2009;Defriez et al 2016;Shestakova et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The propagule bank spreads recruitment over multiple potential growing seasons through long term dormancy and delayed development, thereby buffering populations against unfavorable growing seasons and demographic catastrophes [ 10 , 11 ]. Both empirical and modelling studies demonstrate that propagule banks are crucial for the resilience of populations, especially when growing seasons are often unsuitable for successful reproduction [ 7 , 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that propagule banks will be vital for organisms such as freshwater zooplankton to maintain positive long term population growth in the face of climate change [ 12 , 18 , 19 ], little research exists on the possible effects of climate change on propagule banks. For instance, it is mostly unknown whether propagule survival would be affected by realistic changes in current temperatures under climate change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed metamorphosis as a side effect of reduced foraging rates in response to a predation threat observed in Rana tadpoles is no longer observed when complemented with a risk of desiccation (Laurila & Kujasalo, 1999), indicating that the latter stressor has priority. Furthermore, modeling of population growth rates of crustaceans from temporary pools, which have a similar life-cycle to that of Nothobranchius killifish, shows that any delay in maturation has strong negative effects on long-term demographics (Pinceel, Vanschoenwinkel, Brendonck, & Buschke, 2016) (Pinceel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%